Cultivation of Corneal Endothelial Cells on a Pericellular Matrix Prepared from Human Decidua-Derived Mesenchymal Cells - Numata, Ryohei (Public Library of Science, 2014)
The barrier and pump functions of the corneal endothelium are essential for the maintenance of corneal transparency. Although corneal transplantation is the only current therapy for treating corneal endothelial dysfunction, the potential of tissue-engineering techniques to provide highly efficient and less invasive therapy in comparison to corneal transplantation has been highly anticipated. However, culturing human corneal endothelial cells (HCECs) is technically difficult, and there is no established culture protocol. The aim of this study was to investigate the feasibility of using a pericellular matrix prepared from human decidua-derived mesenchymal cells (PCM-DM) as an animal-free substrate for HCEC culture for future clinical applications. PCM-DM enhanced the adhesion of monkey CECs (MCECs) via integrin, promoted cell proliferation, and suppressed apoptosis. The HCECs cultured on the PCM-DM showed a hexagonal morphology and a staining profile characteristic of Na(+)/K(+)-ATPase and ZO-1 at the plasma membrane in vivo, whereas the control HCECs showed a fibroblastic phenotype. The cell density of the cultured HCECs on the PCM-DM was significantly higher than that of the control cells. These results indicate that PCM-DM provides a feasible xeno-free matrix substrate and that it offers a viable in vitro expansion protocol for HCECs while maintaining cellular functions for use as a subsequent clinical intervention for tissue-engineered based therapy of corneal endothelial dysfunction.